Finger dexterity deficits in Parkinson's disease and somatosensory cortical dysfunction. Issue 3 (March 2015) - Foki, Thomas; Pirker, Walter; Geißler, Alexander; Haubenberger, Dietrich; Hilbert, Markus; Hoellinger, Ilse; Wurnig, Moritz; Rath, Jakob; Lehrner, Johann; Matt, Eva; Fischmeister, Florian; Trattnig, Siegfried; et al.
Abstract Introduction The patho-physiological basis for finger dexterity deficits in Parkinson's disease (PD) is controversial. Previously, bradykinesia was regarded as the major mechanism. However, recent research suggested limb-kinetic apraxia as an important component of impaired fine motor skills in PD. In contrast to bradykinesia, limb-kinetic apraxia only marginally responds to dopaminergic treatment. Here we investigate the novel hypothesis that the dexterity deficits are related to an intrinsic dysfunction of primary somatosensory cortex (S1), which is not reversible by dopaminergic medication. Methods Applying a standard and approved dexterity task (coin rotation), brain activation networks were investigated using functional magnetic resonance imaging in PD patients both ON and OFF medication and matched healthy controls. Results PD patients both ON and OFF medication showed impaired S1 activation relative to controls (p < 0.05; region of interest based analysis). The impaired S1 activation remained unchanged by dopaminergic medication. Despite the considerable clinical deficit, no other brain area showed impaired activation. In contrast, structures of the basal ganglia – motor cortex loop responded to dopaminergic medication. Behaviorally, dexterity performance both ON and OFF was significantly (p < 0.05) reduced relative to controls. Conclusions Our results provide first evidence that dexterity deficits in PD are related to an S1 dysfunction which is insensitive to dopaminergic treatment.